2018
DOI: 10.1002/hep.30086
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein‐Induced Protein 1 Targets Hypoxia‐Inducible Factor 1α to Protect Against Hepatic Ischemia/Reperfusion Injury

Abstract: Sterile inflammation is an essential factor causing hepatic ischemia/reperfusion (I/R) injury. As a critical regulator of inflammation, the role of monocyte chemoattractant protein-induced protein 1 (MCPIP1) in hepatic I/R injury remains undetermined. In this study, we discovered that MCPIP1 downregulation was associated with hepatic I/R injury in liver transplant patients and a mouse model. Hepatocyte-specific Mcpip1 gene knockout and transgenic mice demonstrated that MCPIP1 functions to ameliorate liver dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
(109 reference statements)
0
22
0
Order By: Relevance
“…It was also shown that overexpression of Mcpip1 reduces liver injury in septic mice, by inhibiting inflammatory reaction in macrophages [15]. Additionally, Mcpip1 ameliorates liver damage, reduces inflammation, and promotes tissue regeneration in the hepatic ischemia/reperfusion injury model [16].…”
Section: Introductionmentioning
confidence: 97%
“…It was also shown that overexpression of Mcpip1 reduces liver injury in septic mice, by inhibiting inflammatory reaction in macrophages [15]. Additionally, Mcpip1 ameliorates liver damage, reduces inflammation, and promotes tissue regeneration in the hepatic ischemia/reperfusion injury model [16].…”
Section: Introductionmentioning
confidence: 97%
“…Hepatic ischemia-reperfusion (I/R) injury is a complication of hepatic surgery, and it can arise after liver resection and transplantation [1,2]. Hepatic I/R injury induces oxidative stress, inflammation, and other disorders in the liver, thus leading to the liver damage in patients requiring liver surgery [3][4][5][6]. However, the mechanisms underlying the I/R injury are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Last, in extension to the measured AST and ALT levels, a more comprehensive evaluation of the functional outcomes such as short-and long-term survival after liver injury should be part of future studies. Furthermore, for a deeper understanding of the underlying mechanisms of hepatic regeneration after IRI, evaluation of protein levels such as HIF1-α might be an objective for further studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded liver sections for immunohistochemistry were immersed in three changes of xylene and hydrated with a graded series of alcohol. Hematoxylin and eosin staining (H&E) was used to evaluate the regenerative capacity of the liver by determination of Mitotic Index and the liver damage by Suzuki's score [27]. Suzuki's score was obtained by a single blinded pathologist experienced in liver histology.…”
Section: Histologymentioning
confidence: 99%